Management Accounting and Measurement of Environmental Financial Performance at PT. Indo Bali Fish as a Form of Corporate Social Responsibility - I G Y Pradipta; I M Sudana; I W P Suta (Journal of Applied Sciences in Accounting, Finance, and Tax, 2018)
The purpose of this study was to Determine the application of environmental management accounting and financial performance compute environment in PT. Indo Bali Fish. Methods of the data analysis used in this study was a comparative descriptive method and quantitative analysis, by identifying environmental costs and prepare environmental financial statements. Based on the results of the study, showed that PT. Indo Bali Fish have yet to implement environmental management accounting. This is evident from the lack of special treatment for environmental reporting costs at PT. Indo Bali Fish. After calculating the environmental financial performance of the company, the general financial performance of PT. Indo Bali Fish is good but there needs to be some improvements to waste management activities generated in order to have a positive impact both the corporate environment and surrounding communities.